Foreign children in the Polish school. Portrait(s), challenges and problems - Herudzińska, Małgorzata H. (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2018)
School represents a specific cultural borderland, where the particular emphasis should be put on the analysis of the teachers, foreign schoolchildren and their parents as well as other schoolchildren. All this raises many questions. In this paper there is an attempt to answer several of these questions: How are the legal arrangements are adjusted to the foreign schoolchildren presence in the Polish educational system? What kind of competences are required to work with a foreign child? What kind of tasks and problems are imposed on teachers in the presence of foreign schoolchild in the classroom? Are teachers prepared to work with them? What is the scope of such work (e.g. emotional contact with schoolchildren, capability to assess them, to help them study)? When do teacher feel the need for support in work with such schoolchildren? What kind of need is this? What could enhance the integration of foreign and Polish schoolchildren? What are the possibilities for improvement of the cooperation between school and parents of the foreign schoolchildren in teachers’ opinion?
Keywords: migrations; foreign schoolchild; multiculturalism